Droughts in Asian monsoon region - Shaw, Rajib; Nguyên, Huy (Community, environment and disaster risk management ;, 2011)
Drought is a slow-onset disaster. The impacts are invisible and are often reflected as a complex socio-economic phenomenon. Due to changes in the climatic conditions droughts are increasingly occurring in non-traditional drought prone areas. The Asian monsoon region is one of these areas where consecutive years of droughts are causing severe problems for the lives and livelihoods of the communities. The impacts are becoming increasingly more visible, and drawing the attention of policy makers and professionals from national and international levels. In this context, this book outlines the characteristics and challenges of the Asian monsoon drought and highlights innovative solutions and approaches undertaken in different parts of the region. A ready-reference for field practitioners it combines academic research and field practices, and builds on actual implementation experiences of drought risk reduction. Providing a thorough examination of the subject and region, chapters cover droughts in Vietnam, Cambodia, Laos, Thailand, Myanmar, Bangladesh, India and Sri Lanka. It concludes with an article on cross-cutting experiences and drought risk reduction in the Asian Monsoon Region.